1998
DOI: 10.1111/j.1547-5069.1998.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Domestic Violence in Low‐Income Lebanese Families

Abstract: From a cultural perspective, the analysis revealed both strengths and vulnerabilities of Lebanese women who experienced domestic violence. The study raised several questions, including whether it is appropriate to apply Western-generated domestic violence theories to a Middle Eastern population. Culturally-specific nursing interventions should be directed toward bolstering strong family and social resources to cope with family stressors and to modify patterns of maladaptive communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 4 publications
3
32
1
Order By: Relevance
“…However, a fourth study by Dalalet al [37] found the same differences between Muslim and non-Muslim women in all forms of abuse except for physical abuse. Contrary to the findings of the Bangladeshi studies, research conducted with Lebanese women found Armenian women in the study cohort reporting more physical abuse than Muslim women [38]. Yet another study conducted in Nigeria reported that Catholic women experienced significantly higher sexual abuse than Muslim women.…”
Section: Prevalence and Types Of Abusecontrasting
confidence: 47%
See 1 more Smart Citation
“…However, a fourth study by Dalalet al [37] found the same differences between Muslim and non-Muslim women in all forms of abuse except for physical abuse. Contrary to the findings of the Bangladeshi studies, research conducted with Lebanese women found Armenian women in the study cohort reporting more physical abuse than Muslim women [38]. Yet another study conducted in Nigeria reported that Catholic women experienced significantly higher sexual abuse than Muslim women.…”
Section: Prevalence and Types Of Abusecontrasting
confidence: 47%
“…The order of factors identified was similar to original scale. Several qualitative studies discussed interlocking factors such as immigration stressors, isolation, spirituality, racism, sexism, work related stressors, conflict with the husband's family, financial stressors, and alcohol abuse by husband as associated with IPV [38,[44][45][46]. These studies revealed and emphasized the complexity IPV situations often have when additional factors are introduced.…”
Section: Prevalence and Types Of Abusementioning
confidence: 99%
“…It is possible that with the infl uence of Western modernization and the change in social structure, having a spouse who shares similar family and cultural background and therefore gender role perceptions would decrease the potential for confl icts. Indeed, unmet role expectations of the spouse were highlighted in a study conducted among low-income Lebanese families as a reason for family confl ict (Keenan et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as identifi ed by Keenan and colleagues, consanguineous wives may use better suited coping strategies such as negotiation and taking initiative (Keenan et al 1998 ). Additionally, they may benefi t from the support of their extended family members, as the probability is higher for her to be living closer to her family, being married to a relative.…”
Section: Discussionmentioning
confidence: 99%
“…Middle Eastern families, although Keenan, El-Hadad, andBalian (1998), andHaj-Yahia (1999), have documented high rates of wife abuse in Lebanon and Palestine. Neff, Holamon, and Schluter (1995) reported that in a sample of 362 Mexican American participants from low SES backgrounds, 17% of the women reported spousal violence.…”
Section: Witnessing Parental Violence In East Asian South Asian Midmentioning
confidence: 98%